2017
DOI: 10.1159/000475942
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium-Glucose Co-Transporter 2 Inhibitor, Empagliflozin, Protects against Diabetic Cardiomyopathy by Inhibition of the Endoplasmic Reticulum Stress Pathway

Abstract: Background/Aims: This study aimed to determine whether or not the sodium-glucose co-transporter 2 inhibitor, empagliflozin (EMPA), can protect against diabetic cardiomyopathy (DCM) and to elucidate the related mechanism. Methods: Rats were divided into the following four groups: a non-diabetic group; diabetic cardiomyopathy rats without EMPA treatment; and diabetic cardiomyopathy rats with EMPA treatment (low- and high-dose EMPA). Hemodynamic measurements were performed to evaluate left ventricular systolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…Recently, a large number of clinical trials have reported that empagliflozin application improved cardiovascular outcomes in diabetic patients [16,32,33]. Numerous experimental studies on diabetic animals show that empagliflozin predominantly delayed the progression of cardiomyopathy [18,24,25]. In the present study, water intake, urine volume and UGE were significantly enhanced, and the blood glucose and body weight were decreased by empagliflozin, which is consistent with the results of other studies [18,22,23,34].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, a large number of clinical trials have reported that empagliflozin application improved cardiovascular outcomes in diabetic patients [16,32,33]. Numerous experimental studies on diabetic animals show that empagliflozin predominantly delayed the progression of cardiomyopathy [18,24,25]. In the present study, water intake, urine volume and UGE were significantly enhanced, and the blood glucose and body weight were decreased by empagliflozin, which is consistent with the results of other studies [18,22,23,34].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, excessive oxidative stress in diabetes was accompanied by elevated level of apoptosis. Not surprisingly, empagliflozin also alleviated the level of cardiomyocyte apoptosis in diabetic mice, which is also concordant with data from recent publications emphasizing the anti-apoptotic role of EMPA in hearts [24]. Empagliflozin rescues diabetic myocardial microvascular injury via the inhibition of mitochondrial fission [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cardiovascular protection is suggested to be another drug class effect [3]. Potential mechanisms of cardiac protection with SGLT2i include renin-angiotensin system inhibition following decreased total body sodium content, reduced myocardial cytoplasmic sodium and calcium load, anti-apoptotic, anti-inflammatory, anti-oxidant effects, rescue of diabetes myocardial microvascular injuries, and reduced sympathetic overactivity, inactivation of endoplasmic reticulum stress [6,12,[38][39][40][41][42]. In this study, empagliflozin restored upregulation of PPARα and ACADM in SHR fed with high fat diet, reflecting a shift toward beneficial metabolic utilization in lipids oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that dysfunction of mitochondrial energy metabolism plays a crucial role in the pathogenesis of DCM [9]. Mitochondrial uncoupling may represent one mechanism alongside increased oxidative stress and ROS production, that leads to reduced cardiac efficiency and lower ATP generation in diabetic hearts [28][29][30]. In addition, defective energy metabolism in the heart is likely to impair energy-requiring processes such as protein synthesis, maintenance of transmembrane [31].…”
Section: Discussionmentioning
confidence: 99%